PENDEKATAN METAKOGNITIF BERBASIS MASALAH SEBAGAI PEMBELAJARAN MATEMATIKA - Nurfauziah Siregar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2017)
Learning with a problem-based metacognitive approach can grow students' cognitive abilities in solving problems. By solving problems, students can organize and control students' cognitive activities so that students' learning methods are more effective and efficient, and students' thinking patterns become more developed and creative in solving problems. Learning that begins with giving problems fosters students' metacognitive actions, can contribute to building students' character to be aware of their behavior in learning. Metacognition has two components, namely metacognitive knowledge and metacognitive skills. In mathematics learning, students' metacognition can be developed in each phase of problem solving: understanding the problem, planning/determining a problem solving strategy, carrying out the solution as planned, and interpreting/rechecking.